1990
DOI: 10.1016/0014-5793(90)80860-l
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a low‐Mr acidic nuclear protein as prothymosin α

Abstract: We have purified to homogeneity a lij-kDa perchloric acid (PCA)-soluble protein from rat thymus nuclei. This highly acidic protein showed a M, of ca. 30 kDa in acetic acid/urea gels, probabty due to oligomer formation. Sequence analysis of internal tryptic and the~ol~c peptides revealed that the purified protein is, in fact, prothymosin u, a very hydrophilic polypeptide, which has been previously classified as a thymic or immunomodulating hormone. We found that prothymosin G( is a rather abundant nuclear prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0
5

Year Published

1991
1991
2009
2009

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 25 publications
2
12
0
5
Order By: Relevance
“…A down-regulation of the ProT gene by TBTO was also observed in rat primary thymocytes (Baken, personal communication). The Western blot analysis result lends support to the observed downregulation of ProT in the TBTO-exposed cells (Figure 3) though further study is required to shed light on whether ProT selectively binds with another protein, or forms an oligomer on SDS-PAGE electrophoresis as previously reported (Palvimo and Linnala-Kankkunen, 1990;Codero et al, 1992) This small nuclear protein (M r = 12122 Da) is found in all mammalian tissues (Evstafieva et al, 2000).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…A down-regulation of the ProT gene by TBTO was also observed in rat primary thymocytes (Baken, personal communication). The Western blot analysis result lends support to the observed downregulation of ProT in the TBTO-exposed cells (Figure 3) though further study is required to shed light on whether ProT selectively binds with another protein, or forms an oligomer on SDS-PAGE electrophoresis as previously reported (Palvimo and Linnala-Kankkunen, 1990;Codero et al, 1992) This small nuclear protein (M r = 12122 Da) is found in all mammalian tissues (Evstafieva et al, 2000).…”
Section: Discussionsupporting
confidence: 80%
“…A specific interaction of ProT with the basic histone H1 in vitro was previously reported (Papamarcaki and Tsolas, 1994;Karetsou et al, 1998). Alternatively, the observed band may be an oligomeric form of ProT, since previous studies showed that proT exhibits anomalous behavior on SDSelectrophoresis, forming oligomers even under denaturing and reducing conditions (Palvimo and Linnala-Kankkunen, 1990;Codero et al, 1992).…”
Section: Protein Identificationmentioning
confidence: 95%
“…Certain aspects of PTa structure may be useful in understanding the transcriptional regulatory function of PTa. Because of the high acidity of the protein (Palvimo and Linnala-Kankkunen, 1990) it is unlikely to be a DNA binding protein. There are structural similarities between PTa and nuclear proteins known to be involved in chromatin activity, and it has been reported that PTa interacts specifically with histone H1 (Diaz-Jullien et al, 1996;GomezMarquez and Rodriguez, 1998;Karetsou et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Prothymosin ␣ is found in the nuclei of virtually all mammalian cells (17,39,43,58) in amounts which correlate with the proliferative activity of the tissue (24,27). The thymus, with its self-renewing pool of precursor cells (2), is usually the richest source, with large amounts of the protein found in the spleen, lungs, and kidneys (16,32).…”
mentioning
confidence: 99%